2012
DOI: 10.1371/journal.pone.0032405
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Full-Length Enterovirus 71 Strains from Severe and Mild Disease Patients in Northeastern China

Abstract: Human enterovirus 71 (EV71)-associated hand, foot, and mouth disease (HFMD) has been a leading cause of childhood infection in China since 2008. Epidemic and molecular characteristics of HFMD have been examined in many areas of China, including the central and southern regions. However, clinical and genetic characterization of EV71 in the northeastern region of China is scarce. In this study, a series of analyses were performed on seven full-length EV71 sequences from HFMD patients who had either severe or mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 23 publications
2
68
0
Order By: Relevance
“…The AH/08/06 strain is classified as subgenotype C4, which has been the sole viral genetic lineage circulating in the mainland since 2007. The strain used in this study exhibits similar recombination events as many other EV71 isolates in mainland China [39], [40], [41].…”
Section: Discussionmentioning
confidence: 68%
“…The AH/08/06 strain is classified as subgenotype C4, which has been the sole viral genetic lineage circulating in the mainland since 2007. The strain used in this study exhibits similar recombination events as many other EV71 isolates in mainland China [39], [40], [41].…”
Section: Discussionmentioning
confidence: 68%
“…It has been confirmed that large HFMD outbreaks with fatal neurological complications that have occurred since 2008 in China were mainly due to subgenotype C4 of EV71 [26], [60][62]. Enterovirus infections are generally mild, however, they have been implicated to cause a variety of diseases, ranging from asymptomatic infection, herpangina, HFMD, to more severe diseases such as menigoencephalitis, myocarditis, and neonatal sepsis, and possibly fatal encephalitis [34], [42], [49].…”
Section: Discussionmentioning
confidence: 99%
“…In China, large scale EV71 outbreaks associated with acute neurological diseases were occurred in 2008 [25], [58], and since then the outbreak pattern has repeated and exacerbated each year, with increasing morbidity and mortality [27], [59]. It has been confirmed that large HFMD outbreaks with fatal neurological complications that have occurred since 2008 are mainly due to subgenotype C4 of EV71 [26], [60][62].…”
Section: Introductionmentioning
confidence: 96%
“…VP1 genes of isolated EV71 viruses were sequenced and genotyped by phylogenetic analysis using the Neighbor-joining method in MEGA 4 software as described previously [8]. Full genomes of selected EV71 viruses were sequenced for phylogenetic analysis and detection of gene recombination [911]. Backgrounds of reference virus sequences used in the phylogenetic analysis were listed in the Table S1.…”
Section: Methodsmentioning
confidence: 99%